Coordinated FA-MS and SIFT-MS analyses of breath following ingestion of D2O and ethanol: total body water, dispersal kinetics and ethanol metabolism - Španěl, Patrik; Wang, T; Smith, D (Physiological measurement, 2005)
A coordinated study of the dispersal of water between the various body compartments (stomach and gut, blood stream and tissue) and the similar dispersal kinetics of ethanol and its metabolism has been carried out involving two healthy volunteers using flowing afterglow mass spectrometry, FA-MS, and selected ion flow tube mass spectrometry, SIFT-MS. Thus, using these techniques, the variations of HDO and ethanol in breath, measured in successive single exhalations, were followed in real time after the ingestion of measured quantities of D2O and ethanol in proportion to the body weights of the subjects at the dose rates D2O approximately 0.283 g kg-1, ethanol approximately 0.067 g kg-1. During the FA-MS experimental periods (about 2 h), the dispersion of HDO into the body water and finally its equilibration in the total body water is observed from which total body water for each subject was determined. In the SIFT-MS measurements, the dispersion of ethanol into the body water and its loss via metabolism was observed until the physiological (pre-dose) breath level of ethanol for each individual was restored. A simple linear transformation is used to derive the time variations of the blood levels of HDO and ethanol. This has allowed a comparison of the fractions of the ingested ethanol that are metabolized during first-pass metabolism for the two subjects. Thus, in one subject 30% and in the other subject 40% of the ingested alcohol is metabolized in the first 20 min following ingestion. The good time resolution allowed by non-invasive breath analysis ensures that the rates of processes such as ethanol metabolism can be accurately measured. Simultaneous measurements of breath acetaldehyde (largely formed via the ethanol metabolism) and acetone were also performed during the SIFT-MS single breath exhalations.
Keywords: Kinetics; tělesná voda; Deuterium Oxide; ethanol; metabolická clearance; Spirometry; lidé; Financing, Government; Body Water; Breath Tests; Ethanol; hmotnostní spektrometrie s elektrosprejovou ionizací; financování vládou; Metabolic Clearance Rate; aplikace orální; dechové testy; spirometrie; Administration, Oral; oxid deuteria; Spectrometry, Mass, Electrospray Ionization; kinetika; Humans